Cellulose-Based Polymer Composite with Carbon Black for Tetrahydrofuran Sensing - Susana Hernández-López; Enrique Vigueras-Santiago; Miriam Mendoza Mora; José Rurik Farias Mancilla; Erasto Armando Zaragoza Contreras (International Journal of Polymer Science)
This work focused on studying the sensing efficiency of tetrahydrofuran (THF) by composite films made of thin layers of a cellulose-based polymer and carbon black. We analyze the reproducibility, durability, desorption time, and the sensitivity percent as a function of the amount of solvent. Two types of experiments were conducted, (1) progressive sensing test (PST) which consisted of progressively increasing the amount of solvent from 0.1 mL increments up to 1.0 mL and (2) multiple sensing test (MST) where the layers were subjected to consecutive pulses of the same amount of solvent, with a minimum of 0.1 mL and a maximum of 0.4 mL. The response and desorption times were a few seconds, and the sensitivity percent ranged from 1% to 170% and was dependent on the solvent quantity.